Physiological cord clamping: dawn to halt anemia in infancy - Ali, Fasna Liaquath; Maruthupandian, Jasmine; V., Pragadeesh Raja (International Journal Of Community Medicine And Public Health, 2020)
All infants immediately following their birth experience a decrease in hemoglobin which result in varying degrees of anemia termed as physiology or early anemia of infancy. Normally after birth hemoglobin values fall from 14.6 to 22.5 g/dl to 10.0 to 12.0 g/dl within 8 to 10 weeks from age, after which the values gradually increase reaching the normal level at the end of 2 years